Systematic review of pertussis immunisation among Asians. Issue 2 (6th June 2016) - Pal, Moneeta; Goodyear-Smith, Felicity; Exeter, Daniel
Abstract : Purpose: – The purpose of this paper is to provide a review of the literature on pertussis immunisations among the Asian population. Design/methodology/approach: – A systematic review was carried out using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The review performed searches using the keywords: immun*, vaccine* AND whooping cough or Bordetella pertussis OR B pertussis AND Asia*. The search was conducted on four electronic databases, namely, Medline, CINAHL, Embase and Cochrane Database of Systematic Reviews. Findings: – In total, 13 studies of relevance were included in the review after screening 206 articles. The studies were categorised into three literature sections which were: epidemiology of pertussis, vaccine effectiveness studies in Asia and strategies aimed to increase uptake of immunisations against pertussis. Research limitations/implications: – Due to financial constraints, the authors only had access to articles published in the English language and full text articles which may limit the generalisability of the review. Originality/value: – The review is useful in providing insight into the general trends of pertussis immunisations among Asians and in aiding future research in this area.